Comparison between two‐ and three‐dimensional quantitative coronary angiography bifurcation analyses for the assessment of bifurcation lesions: A subanalysis of the TRYTON pivotal IDE coronary bifurcation trial. Issue 3 (24th April 2015) - Muramatsu, Takashi; Grundeken, Maik J.; Ishibashi, Yuki; Nakatani, Shimpei; Girasis, Chrysafios; Campos, Carlos M.; Morel, Marie‐Angèle; Jonker, Hans; de Winter, Robbert J.; Wykrzykowska, Joanna J.; García‐García, Hector M.; Leon, Martin B.; et al.
<x xml:space="preserve">Abstract</x> Background Three‐dimensional (3D) quantitative coronary angiography (QCA) provides more accurate measurements by minimizing inherent limitations of two‐dimensional (2D) QCA. The aim of this study was to compare the measurements between 2D and 3D QCA analyses in bifurcation lesions. Methods and Results A total of 114 cases with non‐left main bifurcation lesions in the TRYTON pivotal IDE Coronary Bifurcation Trial (ClinicalTrials.gov: NCT01258972) were analyzed using a validated bifurcation QCA software (CAAS 5.10, Pie Medical Imaging, Maastricht, the Netherlands). All cases were analyzed in matched projections between pre‐ and post‐procedure. The 2D analysis was performed using one of two angiographic images used for 3D reconstruction showing a larger distal bifurcation angle. In the treated segments (stent and balloon), there were no differences in minimal luminal diameter (MLD) between 2D and 3D, while diameter stenosis (DS) was significantly higher in 2D compared to 3D both pre‐procedure and post‐procedure (53.9% for 2D vs. 52.1% for 3D pre‐procedure, P < 0.01; 23.2% for 2D vs. 20.9% for 3D post‐procedure, P = 0.01). In the sub‐segment level analysis, lengths of proximal main branch, distal main branch, and side branch were consistently shorter in 2D compared to 3D both pre‐procedure and post‐procedure. Using 3D QCA, the anatomic location of the smallest MLD or the highest DS was relocated to a different bifurcation sub‐segment in a considerable proportion of the patients compared to when 2D‐QCA was used (kappa values: 0.50 for MLD, 0.55 for DS). Conclusions Our data showed differences in addressing anatomical severity and location of coronary bifurcation lesions between in vivo 2D and 3D QCA analyses. More studies are needed to investigate potential clinical benefits in using 3D approach over 2D QCA for the assessment of bifurcation lesions. © 2015 Wiley Periodicals, Inc.